2006
DOI: 10.1093/hmg/ddl178
|View full text |Cite
|
Sign up to set email alerts
|

DAPK1 variants are associated with Alzheimer's disease and allele-specific expression

Abstract: Genetic factors play an important role in the etiology of late-onset Alzheimer's disease (LOAD). We tested gene-centric single nucleotide polymorphisms (SNPs) on chromosome 9 and identified two SNPs in the death-associated protein kinase, DAPK1, that show significant association with LOAD. SNP rs4878104 was significantly associated with LOAD in our discovery case-control sample set (WU) and replicated in each of two initial validation case-control sample sets (P<0.05, UK1, SD). The risk-allele frequency of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
83
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(87 citation statements)
references
References 46 publications
2
83
0
Order By: Relevance
“…Linkage disequilibrium at 1q44 was reported in a study of 100 AD cases and 100 controls (Zubenko et al 1998), linkage at 2q22 and 2q24 was detected in a linkage study of 88 LOAD families (Lee et al 2004), and linkage at 9q34 was detected in a study of 466 families (Pericak-Vance et al 2000), close to the 9q33 syntenic region reported here. This 9q33 syntenic region is also close to a major region of interest in human AD on chromosome 9q, but lies slightly outside the 9q21-31 region typically identified with the strongest support, and does not contain the DAPK1 gene recently implicated in an association study (Li et al 2006). Unlike the more extensively reported areas of linkage on human chromosomes 9, 10, and 12, these syntenic human linkage findings have not been replicated by multiple studies, suggesting that they are unlikely to explain a major part of the observed heritability of AD risk.…”
Section: Discussionmentioning
confidence: 76%
“…Linkage disequilibrium at 1q44 was reported in a study of 100 AD cases and 100 controls (Zubenko et al 1998), linkage at 2q22 and 2q24 was detected in a linkage study of 88 LOAD families (Lee et al 2004), and linkage at 9q34 was detected in a study of 466 families (Pericak-Vance et al 2000), close to the 9q33 syntenic region reported here. This 9q33 syntenic region is also close to a major region of interest in human AD on chromosome 9q, but lies slightly outside the 9q21-31 region typically identified with the strongest support, and does not contain the DAPK1 gene recently implicated in an association study (Li et al 2006). Unlike the more extensively reported areas of linkage on human chromosomes 9, 10, and 12, these syntenic human linkage findings have not been replicated by multiple studies, suggesting that they are unlikely to explain a major part of the observed heritability of AD risk.…”
Section: Discussionmentioning
confidence: 76%
“…With relevance to neurobiological mechanisms such as neuronal apoptosis and APP trafficking, early genetic studies of LOAD have identified several candidate genes (e.g. DAPK1 [11] and SORL1 [12,13]), but they are still insufficient to completely reveal the genetic factors for AD. A more thorough and efficient approach is required to study the genetic factors of complex diseases like AD.…”
Section: Introductionmentioning
confidence: 99%
“…29 A genome-wide SNP study reveals the association of DAPK with LOAD. 9 Furthermore, mice with a deletion in DAPK kinase domain exhibit an enhanced spatial memory. 30 Although these studies implicate a potential impact of DAPK on AD, our finding that DAPK enhances MARK-induced tau phosphorylation and tau toxicity provides a molecular linkage of DAPK to tauopathy-related neurodegenerative disorders, such as AD.…”
Section: Discussionmentioning
confidence: 99%
“…1,7,8 A further connection of DAPK to neuronal diseases comes from a largescale genetic study, which identifies the association of two single nucleotide polymorphisms (SNPs) in DAPK with lateonset Alzheimer's disease (LOAD). 9 However, the causal relationship between DAPK and LOAD has not been established.…”
mentioning
confidence: 99%